Nutrient supply and bird predation additively control insect herbivory and tree growth in two contrasting forest habitats - Garibaldi, Lucas Alejandro (2010)
Fil: Garibaldi, Lucas Alejandro. Universidad Nacional del Comahue. Centro Regional Universitario Bariloche. Laboratorio Ecotono; Argentina.